Partisipasi Masyarakat dalam Pengembangan Objek Wisata Goa Lowo Berbasis Ekonomi Kerakyatan (Studi Kasus di Desa Tegalrejo, Kecamatan Kelumpang Hilir Kalimantan Selatan) - Nur Safitri, Maulida; Rahmini, Noor (PPJP ULM, 2024)
This study aims to determine community participation in the development the Lowo Cave Tourist Attraction in Tegalrejo Village. Data collection techniques in the form of observation, interviews using questionnaires and documentation with total of 40 respondents. The results of the study show that community participation the development of Goa Lowo tourism object which is supported by the village government is very good. This can be seen: community participation decision making is 81.25% high category, community participation implementing activities is 83.13% high category, community participation monitoring and evaluation is 86.88% high category, and participation community the utilization of the results 88.12% high category.